(untitled) (Global Journal of Human-Social Science, 2012)
Education is considered a key variable not only for widening intellectual horizon of the individual but it also helps a person to make use of coherent and scientific approaches to different problems But eventually there are marked differences in the literacy rate among the sexes in our country The differential literacy rate among men and women indicates the existence of discriminatory practices against women In terms of literacy rate viz age sex and rural urban background it is evident that a female child is neglected and denied the basic civic amenities Regarding educational status empirical researches point out that the level of literacy among women in general and Scheduled Caste women in particular are significantly low The reasons are varied The socio- economic factors like lack of awareness on the relevance of education gender disparity lack of incentive and low paid laborious occupations etc causes poverty and illiteracy which in effect also results in gender gap in literacy